2016
DOI: 10.1097/gox.0000000000001180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Axonal Trauma on Nerve Regeneration in Side-to-side Neurorrhaphy: An Experimental Study

Abstract: Background:Side-to-side (STS) neurorrhaphy can be performed distally to ensure timely end-organ innervation. It leaves the distal end of the injured nerve intact for further reconstruction. Despite encouraging clinical results, only few experimental studies have been published to enhance the regeneration results of the procedure. We examined the influence of different size epineural windows and degree of axonal injury of STS repair on nerve regeneration and donor nerve morbidity.Methods:Three clinically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This method has been used both in isolation and in conjunction with the other repair techniques of ETE and ETS ( Figure 7 ). There has been a combination of multiple animal studies and a smattering of human studies, published on this relatively new method [ 55 , 56 , 57 , 58 , 59 ]. In 1999, Yuksel et al performed side-to-side nerve coaptation procedures between the peroneal and tibial nerve trunks of ten rats and demonstrated that axonal passage was possible with side-to-side nerve neurorrhaphy.…”
Section: Side-to-side Nerve Coaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…This method has been used both in isolation and in conjunction with the other repair techniques of ETE and ETS ( Figure 7 ). There has been a combination of multiple animal studies and a smattering of human studies, published on this relatively new method [ 55 , 56 , 57 , 58 , 59 ]. In 1999, Yuksel et al performed side-to-side nerve coaptation procedures between the peroneal and tibial nerve trunks of ten rats and demonstrated that axonal passage was possible with side-to-side nerve neurorrhaphy.…”
Section: Side-to-side Nerve Coaptationmentioning
confidence: 99%
“…One possible explanation has been proposed by Napoli et al, who developed a mouse model in which the activation of the Ras-MAP signaling pathway was sufficient to initiate SC dedifferentiation without axonal injury [ 56 ]. In this pathway, Ras activates the proto-oncogene serine threonine protein kinase Raf, which then activates mitogen-activated protein kinase-kinase (MEK), in turn promoting the mitogen-activated protein kinase (ERK) signaling that maintains the dedifferentiated state of SCs ( Figure 8 ) [ 58 , 59 , 60 ].…”
Section: Side-to-side Nerve Coaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search to repair such lesions, the end-to-side neurorrhaphy technique was described in the literature as an alternative when it is impractical to apply direct grafts [7,8]. The sural nerve can be used as a donor of fibers and applied in the end-to-side neurorrhaphy technique, since its morphology and growth in symmetry would be a suitable model for experimental studies in neuropathies [9].…”
Section: Introductionmentioning
confidence: 99%